Accuracy Testing of the MAX30100 Sensor Using the Contec MS100 SpO2 Simulator - Bangkit Novalino Wibowo; Rum Sapundani (UM Purwokerto Press, 2026)
The accuracy of pulse oximeters is critical for reliable health monitoring. The MAX30100 sensor is widely used in wearable devices to measure SpO2 and pulse rate. However, its accuracy needs to be assessed against reliable standard devices. The Contec MS100 simulator is used as a benchmark to evaluate the performance of such sensors. A descriptive quantitative study was conducted with a sample of 347 participants. Data were collected from both the MAX30100 sensor and the Contec MS100 simulator to measure SpO2 and pulse rate. The Bland-Altman method and Kruskal-Wallis test were used for statistical analysis to assess the accuracy and agreement between the two devices. The study found that the MAX30100 sensor provided reliable measurements for both SpO2 and pulse rate. The mean difference between the MAX30100 and Contec MS100 was 0.45% for SpO2 and 0.5 bpm for pulse rate. The Bland-Altman analysis showed acceptable limits of agreement for both parameters. However, minor discrepancies were observed. The study found that the MAX30100 sensor provided reliable measurements for both SpO2 and pulse rate. The mean difference between the MAX30100 and Contec MS100 was 0.45% for SpO2 and 0.5 bpm for pulse rate. The Bland-Altman analysis showed acceptable limits of agreement for both parameters. However, minor discrepancies were observed.